Mitochondria - Pon, Liza A.; Schon, Eric A. (Amsterdam, Netherlands Elsevier/Academic Press, 2007)
This book provides an update on the step-by-step "how to" methods for the study mitochondrial structure, function, and biogenesis contained in the successful first edition. As in the previous edition, the biochemical, cell biological, and genetic approaches are presented along with sample results, interpretations, and pitfalls from each method.--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mitochondria; Electronic books